Overweight and Obesity, Body Fat, Waist Circumference, and Anemia in Peruvian University Students: A Cross-Sectional Study - Ruth B. Quiliche Castañeda; Josué Turpo-Chaparro; Jesús Hanco Torres; Jacksaint Saintila; Percy G. Ruiz Mamani (Journal of Nutrition and Metabolism)
The university represents a critical space for students in terms of prevalence of malnutrition. The objective of this study was to determine the body mass index (BMI), body fat percentage (% BF), waist circumference (WC), and anemia in university students. A cross-sectional study was carried out in 2,285 university students from Lima, Peru. The sample was selected by nonprobability convenience sampling. Anthropometric data and hemoglobin levels were measured. The Chi-square test was used. The analysis of the associated factors was done using binary logistic regression. A significance level of 5% was considered. There were no significant differences between men and women in BMI (p>0.05). The men presented significantly high and very high levels of % BF (p<0.001). The proportion of women who presented anemia and high and very high WC was significantly higher compared to men (p<0.001). Being older than 27 years (ORB = 2.07; 95% CI = 1.19–3.6), being male (ORB = 2.68; 95% CI = 2.02–3.55), studying at the engineering faculty (ORB = 1.39; 95% CI = 1.09–1.79), having excess body fat (ORB = 8.17; 95% CI = 6.13–10.87), and having an elevated WC (ORB = 35.51; 95% CI = 25.06–50.33) significantly predicted overweight/obesity. The findings of this study suggest that college students, especially males and those who are not enrolled in health sciences colleges, should be a priority in healthy lifestyle interventions, particularly nutritional education programs, to reduce the prevalence of overweight and obesity.